2021
DOI: 10.3390/pharmaceutics13050705
|View full text |Cite
|
Sign up to set email alerts
|

Tambjamines and Prodiginines: Biocidal Activity against Trypanosoma cruzi

Abstract: The aim of this work was to explore new therapeutic options against Chagas disease by the in vitro analysis of the biocidal activities of several tambjamine and prodiginine derivatives, against the Trypanosoma cruzi CLB strain (DTU TcVI). The compounds were initially screened against epimastigotes. The five more active compounds were assayed in intracellular forms. The tambjamine MM3 and both synthetic and natural prodigiosins displayed the highest trypanocidal profiles, with IC50 values of 4.52, 0.46, and 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…There is wide experimental evidence of the potential use of PG against neglected diseases, such as Chagas disease, amebiasis, and malaria [ 84–86 ]. It was suggested that the mechanism by which PG may act is by triggering mitochondrial dysfunction.…”
Section: Biological Activities Of Prodigiosinmentioning
confidence: 99%
“…There is wide experimental evidence of the potential use of PG against neglected diseases, such as Chagas disease, amebiasis, and malaria [ 84–86 ]. It was suggested that the mechanism by which PG may act is by triggering mitochondrial dysfunction.…”
Section: Biological Activities Of Prodigiosinmentioning
confidence: 99%
“…24−26 In addition, these natural and synthetic compounds have been extensively investigated for various therapeutic applications, including antimicrobial, 27−29 anticancer, 30−35 antitumor, 27,29,36 and immunosuppressive 37 activities with various MoA. 38−41 Indeed, a recent study demonstrated the effectiveness of both TAs and PGs against the kinetoplastid parasites such as Trypanosoma cruzi, 42 the causative agent of Chagas disease. To the best of our knowledge, the exact MoA are unknown for these novel TA chemotypes; however, they likely induce mitochondrial swelling and lysosomal dysfunction leading to autophagy and necrotic cell death in cancer cells.…”
Section: ■ Introductionmentioning
confidence: 99%
“…3–5 In particular, potential applications of these compounds as antimicrobial, antiparasitic or anticancer agents have been reported. 6–10 Applications as transmembrane protein surrogates as potential candidates for the treatment of diseases caused by defective transmembrane anion transport, like cystic fibrosis, have also been explored. 11,12…”
Section: Introductionmentioning
confidence: 99%